FACTORS CAUSING HISTORY TEACHERS’ DIFFICULTIES IN DEVELOPING INSTRUCTIONAL TEACHING IN SLEMAN REGENCY, YOGYAKARTA - Wina Kyky Novianti; Sugiyono Sugiyono (Universitas Negeri Yogyakarta, 2018)
ABSTRACT The method used is qualitative method. Research aims: (1) the profile of teachers who have difficulty, (2) factors – factors that cause difficulties teachers, (3) the similarity of difficulties teachers in developing a learning device, (4) the impact of the factors that lead to teacher trouble, (5) a teacher's efforts in developing a learning device. Results of the study include a profile of teachers examined there were seven teachers live in Yogyakarta, the difficulty factor of teachers in developing a learning device on a promissory note and prota clashed with hours of teaching, the RPP does not match field, the limited infrastructure, the similarity of difficulties teachers develop learning devices: the time the making of RPP, the limited infrastructure, the impact posed namely teachers less ready in the delivery of the learning material, not optimal , work done: MGMP, participation and training. Keywords: teacher learning device, difficulty, effort, the impact. Keywords: teachers’ difficulties, learning kits, efforts, impacts